TECHNOLOGIES OF LANGUAGE TEACHING METHODS (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2023)
This article provides insights into language teaching methodology technologies. It shows the stages of development of educational technologies in teaching mother tongue in Uzbekistan. The problem of mother tongue curriculum was identified as a separate topic, it was argued that it is a topical methodological problem, and its form, methods and tools were identified.